Hubungan Waktu Pemberian Ebtifibatide dengan TIMI Flow Infarct Related Artery pada Intervensi Koroner Perkutan Primer - Abdul Hakim Alkatiri; Yoga Yuniadi; Dicky A Hanafy; Doni Firman; Sunarya Soerianata (The Indonesian Heart Association, 2011)
Background. Optimal administration timing of Glicoprotein IIb/IIIa inhibitor in STEMI patients undergoing Primary PCI is controversial. Several stud -ies have shown that early administration of eptifibatide, which is given to patients with pain awitan of < 90 minutes will improved TIMI grade flow of infarct related coronary artery (IRA). However, significant numbers of patient arrived in emergency room/PCI center with pain awitan of > 3 hours. This study was aimed to evaluated effect of eptifibatide administra-tion timing to TIMI grading flow in first angiographic IRA during primary PCI in patients with STEMI.Methods and result. Of 116 consecutive STEMI patients who underwent primary PCI, 79 patients received ebtifibatide < 90 minutes (Group 1) and 37 patients received eptifibatide > 90 minutes (Group 2) before first angiographic of IRA. There were no significant differences of TIMI 3 flow proportion after PCI between the groups (86.1% vs 83.8% for Group 1 and 2 respectively, p = 0.745). Group 2 showed more frequent TIMI 2 flow (18.9% vs 5.1%, p = 0.036) but tend to have less frequent TIMI 0 flow (56.8 % vs 67.1%, p = 0.281).Conclusion. Patients who received eptifibatide > 90 minutes before first angiographic IRA during primary PCI achieved more appropriate TIMI flow as compare to that received eptifibatide < 90 minutes.